ANALISIS PENGARUH POLUSI CAHAYA TERHADAP CITRA FAJAR SEBAGAI AWAL WAKTU SALAT DI PANTAI MALLENRENG DAN PANTAI BULOKKONG - Hasbullah, Jihan Nashirah; Syarif , Muh. Rasywan (Universitas Islam Negeri Alauddin Makassar, 2025)
Abstract This article discusses the impact of light pollution on the dawn image as the beginning of the Fajr prayer time in East Sinjai, Sinjai Regency, with two sub-issues: The influence of light pollution on the dawn image as the beginning of the Fajr prayer time in East Sinjai District, Sinjai Regency and The state of the dawn image as a determinant of the beginning of Fajr prayer time during excessive light pollution in East Sinjai District, Sinjai Regency. This type of research uses field research with a qualitative approach, where the researcher conducts direct observations of the study objects in the field. The researcher employs literature, religious and astronomical approaches. In data processing, this study is conducted in three stages: field observation, interviews with local residents and tourists and lastly documentation of the conditions in the research field. The results of the study at two locations, namely Mallenreng Beach and Bulokkong Beach, found the preliminary Fajr prayer time in East Sinjai District, Sinjai Regency, to be at 04:25 and 04:26, showing the dawn ṣhadiq using the ImageJ application, while the time differs from the Fajr call to prayer at nearby mosques (Masjid Al Ikhlas, Subulussalam, Rayatul Falah, and Jami’ Majmullatif), which is at 04:36. This is caused by high-category light pollution present in the research location. The implications of this research suggest that light users should reduce and promptly turn off lights so that travelers are not hindered when observing the dawn ṣhadiq, and there should be a